HOTS Development Strategy through Project Based STEM Learning at High School Level - Yennita, Y; Irianti, Mitri; Zulirfan, Z; Yoeliana, Rosa (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aims to analyze the effect of STEM project based learning on improving students' higher-order thinking skills. The research method used is a quasi-experimental design with a non-equivalent posttest only control group design. The population of this study was all 130 students of grade XII. Then the sample was taken randomly obtained XII IPA 3 as the control class and XII IPA 4 as the experimental class. This study used test instruments in the form of essay questions and HOTS multiple choices. Data were analyzed using the SPSS program. The results of the study obtained a sig. 0.027 ≤ 0.05 meaning that the results obtained in the study were that there were significant differences in higher-order thinking skills between classes using STEM project-based learning and classes using conventional learning. Based on these results, STEM project-based learning can improve high school students' higher order thinking skills. These findings indicate that STEM PjBL can function as an effective model to improve analytical, evaluative, and creative capacity in learning in high school.